Black and white fire: the interplay of stories, imagination and children's spirituality - Trousdale, Ann M. (International journal of children's spirituality, 2004)
This paper explores the potential for using narrative to foster children's spiritual growth. It discusses the nature, origin and appeal of story and presents theoretical perspectives which form a rationale for using non‐sectarian children's, adolescent and young adult literature for spiritual development. Such books avoid church‐and‐state controversies while providing a fresh approach to educators where religious and spiritual education are mandated.